UPAYA PENINGKATAN MOTIVASI BELAJAR PKN SISWA KELAS IV SD NEGERI 011 PAGARAN TAPAH DARUSSALAM MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY - Misnawati ' (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This research is motivated by the lack of motivation to learn civics fourth grade students ofSD Negeri 006 Pagaran Tapah Darussalam. This study aims to determine whether themotivation to learn civics fourth grade students of SD Negeri 011 Pagaran TapahDarussalam can be enhanced through the implementation of cooperative learning model TwoStay Two Stray, which is carried out for 1 month. Subjects in this study is the fourth gradestudents of SD Negeri 011 Pagaran Tapah Darussalam 2016-2017 school year the number ofstudents as much as 6 students, consisting of 4 boys and 2 girls. Form of research isclassroom action research. The research instrument consists of instruments and instrumentperformance data collection activity observation sheet form teacher and student activity.Based on the analysis and discussion as presented in chapter IV can be concluded that theapplication of the method two only two guests can enhance students' motivation fourth gradeon the subjects of citizenship education in primary schools Tapah 011 Pagaran Darussalam.It can be seen from changes in student motivation in cycle 1 and cycle 2. Students 'motivationin the first cycle is 15 with an average of 41.7 students' motivation in lower categories and anincrease in cycle 2 to 31 with an average of motivation to learn 86.1 students in the very highcategory. Based on the performance indicators that this research is successful if it reaches75% of all students